Desinclusión de Dientes Retenidos mediante Aparatología Removible - Soldevilla Galarza, Luciano Carlos (2003)
The diagnostic and treatment of the pieces held its necessary, to avoid later complications that could endanger the dental arc integrity. Therefore we are planning a multidisciplinary work that will include an early evaluation of the piece until the are will be in perfect line up using the Odontopediatrics and Surgery services (as a first stage). The traction orthodontic with removing devices; later to the surgery exposition could be unique or propose like the first part of the treatment more complex in agreement with the necessity of each patient. In this article we propose a short theory and the proposal of one clinic case of patient who arrived to the service of the Faculty in 2002.